2022
DOI: 10.1016/j.ultsonch.2022.105910
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of regimes determining sonochemical reactions in solid particle suspensions

Abstract: Highlights Effect of particle size and concentration on sonochemical yields were examined. The site-increasing regime and the sound-damping regime are clarified. Adding microparticles changed from being enhancing to inhibiting at ∼ 1 vol%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…I 3 − production linearly increased with ultrasonic irradiation time in the test solution containing either silica particles or argon gas bubbles, as well as in the single-phase case ( Fig. 5 ), which is well aligned with the results of past studies [45] , [52] . This indicates that the formation rate of I 3 − , r f (I 3 − ), defined as the increase in I 3 − concentration per unit time, was independent of the irradiation time (≤25 min).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…I 3 − production linearly increased with ultrasonic irradiation time in the test solution containing either silica particles or argon gas bubbles, as well as in the single-phase case ( Fig. 5 ), which is well aligned with the results of past studies [45] , [52] . This indicates that the formation rate of I 3 − , r f (I 3 − ), defined as the increase in I 3 − concentration per unit time, was independent of the irradiation time (≤25 min).…”
Section: Resultssupporting
confidence: 90%
“…They ascribed this to additional nucleation sites, as well as titania’s catalytic activity [42] . Her et al [43] found that ⋅OH yields in 3–12-vol% glass bead suspensions were lower than those in water, and decreased with increasing solids fraction, which tallied with the results of other studies [44] , [45] . In more concentrated suspensions, gas/vapor diffusing through the bubble wall would be harder, which would in turn make it harder for bubbles to oscillate or collapse [46] .…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Fig. 12 displays the measurement findings, and we performed a linear fit to the results, and the slope of the fitted straight line is the production rate of H 2 O 2 ( ), μM/min) [39] , which would be used in the following section to estimate the number of active bubbles. was 0.27 μM/min or 0.06 μM/min under 20 kHz ultrasound (210 W/L) or 80 kHz (85.4 W/L) ultrasound, respectively.…”
Section: Mechanism Of Tetracycline Degradation By the Combination Of ...mentioning
confidence: 99%
“…Hydrophobic particles work more effectively as cavitation nuclei compared to hydrophilic particles [ 98 , 99 ]. In summary, the number, size, and hydrophobicity of impurity particles determine the acoustic cavitation threshold (or number of cavitation bubbles) [ 100 ].…”
Section: Acoustic Cavitation Thresholdmentioning
confidence: 99%